Perancangan Lampu Otomatis Menggunakan Sensor Cahaya Dan Timer Berbasis Arduino Uno - Prita Niken Puspita; Muhajir Syamsu; Vany Terisia (Jurnal Teknologi Informasi (JUTECH), 2023)
People's lives are busy with activities outside the house, often crushing small things like turning the lights off, doing outdoor activities until late at night, dark housing conditions are very potentially criminal. The technology used to solve such problems is something of an automatic nature. Automatic technology is a home light that can turn on and off automatically. The method used is a qualitative method that has descriptive properties, i.e. the researcher describes a phenomenon with accurate data and is systematically studied. Automatic light design with a light sensor that inserts a program in an Arduino uno module that can give instructions of light on and off. The light sensor connected to the relay as an automatic switch is heavily dependent on the light resistance value received by the light sensor. When the light sensor receives less than 200, the light goes off. When at night the resistance values received by a light sensor are more than 200 then the light is automatically lit. The automatic light design uses the Light Dependent Resistor (LDR) light sensor module that can automatically turn off the light through the resistant value received from the light Sensor, and can use the timer as a form of system development when the light becomes uncertain and occurs in the rainy season. A timer can direct the schedule to turn on and off the lights as needed.